Scalable, colloidal synthesis of SnSb nanoalloy‐decorated mesoporous 3D NiO microspheres as a sodium‐ion battery anode. (28th October 2021) - Verdianto, Ariono; Lim, Hyojun; Kang, Jin Gu; Kim, Sang‐Ok
Summary: Sodium‐ion batteries (SIBs) have attracted significant attention for their potential to replace lithium‐ion batteries, owing to the low cost and natural abundance of sodium resources. Alloy‐type anode materials like Sn and Sb possess high theoretical capacities, but they suffer from several shortcomings associated with large volume expansion and electrode disintegration during cycling. Herein, we report SnSb nanoalloy‐decorated mesoporous 3‐dimensional (3D) NiO microspheres that are prepared using a simple, scalable, colloidal chemistry route. The in situ formed SnSb nanoalloy offers enhanced sodiation/desodiation reversibility and improved electrode kinetics through fast ionic/electronic transport. Moreover, the mesoporous structure of the NiO microspheres serves as a robust structure‐reinforcing matrix that alleviates the huge volume change of the SnSb nanoalloy and prevents particle agglomeration during sodiation/desodiation. Owing to the synergistic effects of nanosizing and nanoconfinement, this unique microsphere architecture, wherein the SnSb nanoalloys are uniformly distributed within the mesoporous 3D NiO matrix, delivers a high reversible capacity of 315 mAh g −1 with significantly improved cycle and rate performances compared with those of bulk SnSb. This facile, synthetic approach and the enhanced sodium‐storage performance of our composite microspheres allow for the design and realization of high‐capacity alloying‐type anodes for SIBs and versatile composite materials for energy storage applications. Abstract : In this study, porous SnSb/NiO microsphere is synthesized via a facile, scalable colloidal route and employed as a sodium‐ion battery anode. Formation of SnSb nanoalloy leads to fast electrode kinetics by shortening the diffusion path, and mesoporous NiO enables nanoconfinement of SnSb and prevents self‐agglomeration. The resultant SnSb/NiO microsphere exhibits high sodiation/desodiation reversibility with good cycling and rate performance.